Fuel cell plus STATCOM as synchronous generator in modern power systems - Dogan, Kivanc; Gungor, Melike Esen; Orhan, Ahmet; Ozdemir, Mehmet (Pergamon-Elsevier Science Ltd, 2024)
Synchronous generators have a significant role in the power system for active and reactive power control. However, the increasing usage of inverter-based power distribution systems, along with the growing prominence of renewable energy sources, raises concerns about their reliability and stability. The objective of this study is to address the reactive power load demands by employing a Static Synchronous Compensator (STATCOM) in a grid with a fuel cell stack. To reduce the threat posed by the use of inverter-sourced power transmission elements on power systems, a combined fuel cell and STATCOM structure is proposed and it is shown in the MATLAB/Simulink environment that this structure has the dynamic characteristics of a synchronous generator. This study emphasizes that the fuel cell+STATCOM structure can be used as a synchronous generator and presents a different approach in the literature. The system comprises the fuel cell, harmonic filter, STATCOM, load, coupling inductances, measurement units, and PI controller. This system is aimed to create a system that can operate stably in different reactive power requirements and meet the determined reactive power requirement in any case. This study aims to meet the need for large power synchronous generators.
Keywords: Fuel cell; Synchronous generator; STATCOM; Active and reactive power control